2017
DOI: 10.1016/j.jmb.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Alternative Polyadenylation (APA) within the Drosophila Nervous System

Abstract: Alternative polyadenylation (APA) is a widespread gene regulatory mechanism that generates mRNAs with different 3′-ends, allowing them to interact with different sets of RNA regulators such as microRNAs and RNA-binding proteins. Recent studies have shown that during development, neural tissues produce mRNAs with particularly long 3′UTRs, suggesting that such extensions might be important for neural development and function. Despite this, the mechanisms underlying neural APA are not well understood. Here, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Like most eukaryotic genes, the 3′ UTRs of RPGs are longer and more heterogeneous in size than the 5′ UTRs. Alternative 3′ end formation and/or polyadenylation, which modify the position of the mRNA 3′ end, have been recorded for eukaryotic RPGs, including those in yeast and metazoan (Antione & Fried, 1995; Chakrabarti, Dinkins, & Hunt, 2018; Gudipati, Neil, Feuerbach, Malabat, & Jacquier, 2012; Parenteau et al, 2015; Stevens, Howe, & Hunt, 2018; Vallejos Baier, Picao‐Osorio, & Alonso, 2017). The relatively short size of RPGs 5′ UTRs may reflect the need for efficient translation, while the long and heterogeneous 3′ UTRs may provide opportunities for gene regulation.…”
Section: Rpgs Structure Organization and Distributionmentioning
confidence: 99%
“…Like most eukaryotic genes, the 3′ UTRs of RPGs are longer and more heterogeneous in size than the 5′ UTRs. Alternative 3′ end formation and/or polyadenylation, which modify the position of the mRNA 3′ end, have been recorded for eukaryotic RPGs, including those in yeast and metazoan (Antione & Fried, 1995; Chakrabarti, Dinkins, & Hunt, 2018; Gudipati, Neil, Feuerbach, Malabat, & Jacquier, 2012; Parenteau et al, 2015; Stevens, Howe, & Hunt, 2018; Vallejos Baier, Picao‐Osorio, & Alonso, 2017). The relatively short size of RPGs 5′ UTRs may reflect the need for efficient translation, while the long and heterogeneous 3′ UTRs may provide opportunities for gene regulation.…”
Section: Rpgs Structure Organization and Distributionmentioning
confidence: 99%
“…In summary, eight model genes were used in the gene set for this analysis, and it was found that they were regulated by multiple transcription factors and other common mechanisms [37][38][39]. Transcription factor NFAT5 was the main regulator of gene concentration, and there was statistical significance in the difference of survival prognosis and immune cell infiltration in LUAD (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Since transcripts from more than 70% of human genes are alterna7vely polyadenylated under one condi7on or another, APA is widespread (Gruber and Zavolan 2019). The most intriguing cases are those where the choice of 3' end cut site is developmentally regulated, leading, for example, to produc7on of transcripts with longer 3'UTRs from specific genes in neurons or shorter 3'UTRs in differen7a7ng male germ cells compared to precursor cells (Hilgers et al 2012;Miura et al 2013;Shan et al 2017;Vallejos Baier et al 2017;Grassi et al 2019;Berry et al 2022).…”
Section: Introduc/onmentioning
confidence: 99%
“…The site at which 3' end cleavage will take place is guided by recogni7on by CPSF through the components CPSF30 and WDR33 of the polyadenyla7on signal (PAS), an hexamer (most commonly AAUAAA or a close variant) in the nascent mRNA usually ~15-30 nucleo7des upstream of the cleavage site (Clerici et al 2018;Gallicchio et al 2023). While the central role of the core complex CPSF in recognizing the PAS and cleaving the nascent mRNA molecule is rela7vely clear, the specific contribu7ons of the other complexes and associated factors in specifying whether, where, on what specific gene products, and in which cell types a cut is made is under inves7ga7on (Vallejos Baier et al 2017;Zhu et al 2018;Turner et al 2020).…”
Section: Introduc/onmentioning
confidence: 99%